Transfer Of Legal Protection Against Creditors Fiduciary Insurance Object Without Approval By The Creditors - Lutfia Syalwa Rufaida; lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Fiduciary transfer of ownership rights is an object that made the object of a guarantee on the basis of trust with the provisions fiduciary objects remain in the possession of the owner of the object. However, the implementation of Act No. 42 Of 1999 on Fiduciary for this still requires attention, especially for the protection of creditors. Aiming to analyze the legal protection acquired by the creditor against the acts committed by the debtor, namely the transfer of fiduciary security object without the consent of creditors as well as to determine the legal consequences arising method used in analyzing these issues is normative juridical research. The method is a normative legal research done by researching library materials or secondary materials. Through this method is expected to provide a comprehensive understanding of the relevant legal protection for creditors. Based on the analysis showed fiduciary creditors as the recipient requires legal certainty to the object as collateral because it will hinder the process of execution when security object transferred by the debtor without the consent of the creditor. Article 23 paragraph (2) of the Act Fiduciary that the debtor may assign without the prior written consent of the Receiver fiduciary. So from these provisions can be considered that the debtor has committed an unlawful act that clearly there are provisions in article 36 of Law Fiduciary related penalties obtained by the debtor. Keywords: Legal Protection; Creditor; Fiduciary Transfer.